Capacity Building for Community Development among Educators in Guatemala (Global Journal of Human-Social Science, 2013)
This study reports on a multi-year capacity building research partnership between the Center for Child and Community Development a Guatemalan non-profit and public schools in State of Sacatep quez in Guatemala We explore finding from phase 1 of the research involving a survey study and capacity building activities with 39 elementary school teachers The surveys examined a teacher professional develop-ment b instructional strategies c resources needed and d parent community involvement The findings suggest that socio-economic differences levels of teacher preparation linguistic and cultural issues are the key points of leverage that need to be addressed through capacity building activities for Guatemalan educators The findings also provide contextual evidence for future program planning and curriculum implementation across public schools in rural and urban areas
Keywords: capacity building; intercultural bilingual program; socio-cultural teaching and learning